Wastewater treatment in dry climates (desert or desert with some rain) - Hammer, Mark J., 1931- (Water Environment Federation, 2001)
This publication details the most appropriate unit processes for wastewater treatment in a dry climate, which is defined as a desert or a desert with some rain. The knowledge and technology revealed in this book comes from years of extensive research in Saudi Arabian wastewater treatment plants. The research reveals dramatic effects on treatment processes in hot, dry climates resulting in high wastewater temperatures. Evaluations of these treatment plants show that the primary cause of operational problems results from the application of inappropriate design standards, or those intended for plants located in temperate climates. An invaluable reference and research tool, this publication also incorporates problems and solutions so that it can be used as a college textbook. Learn about design considerations, wastewater treatment, sludge processing, and methods of treating wastewater for disposal or reuse in dry climates. -- Provided by publisher.
Keywords: Sewage -- Purification -- Arid regions.; elektronické knihy; electronic books